EDUCATION ACCORDING TO THE CONCEPT OF THE Q.S. AL-BAQARAH verse 31 - Putra Mahendra Gunawan Nasution (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2023)
ABSTRACTThis study aims to understand the explanation of education according to the Qur'an which refers to Q.S. Al-Baqarah: 31. This research is a library research. The method and focus on this analysis were used in analyzing the data. This research method uses a qualitative descriptive approach in the form of words or language by utilizing various scientific methods. This study discusses education according to Q.S. Al-Baqarah: 31, namely Allah has taught Adam (as) the names of all objects, then Allah showed the angels, saying, "Mention to me the names of all these (objects), if you are right!". However, the angels were unable to answer, so Allah made Adam (as) the Caliph on this earth by teaching the names of all objects that exist on this earth because Allah knows best what the angels do not know. The results of the research are, if education according to the concept of the Qur'an is associated with human life, that studying is very important so that humans have knowledge and become Caliphs (leaders) on this earth and do not do damage on this earth with the knowledge they have.